Experimental Study on the Suppression of Cavity Noise in a Locking-On State by a Slanting Inner Wall - Yuan Liu; Peiqing Liu; Hao Guo (Aerospace)
This paper presents an experimental investigation into the noise characteristics of various slanted wall configurations. The study focuses on the noise suppression effects of cavities with slanted walls on cavity coupling noise. A total of eight configurations, with different slanting angles on the front and rear walls, were analyzed by varying the inclination of the inner wall. Noise and flow field measurements were conducted in an aeroacoustic wind tunnel, utilizing microphones for near-field and far-field noise data acquisition and hot-wire probes for flow field analysis. The results indicate that larger slant angles lead to more effective noise reduction. As the slant angle increases, the acoustic resonance frequency associated with the slanted inner wall rises, which alters the self-excited oscillation modes involved in coupling with the acoustic resonance. This reduces the impact of coupling on the sound pressure levels. The change in acoustic resonance frequency also modifies the phase delay term of the dominant mode, ultimately leading to a shift in the noise frequency.